المجاهد الأزهاري عوينات؛ حياته ونضاله الوطني (1930-2006م) - خديجة نصيرة; زينب عقاب (جامعة الوادي - University of Eloued, 2025)
"ولد المجاهد الأزهاري عوينات سنة 1930 م , بقرية حاسي خليفة , حرص على حفظ كتاب الله منذ صغره , وعندما أصبح شابا هاجر إلى البلاد التونسية بحثا عن لقمة العيش, وهروبا من السياسة الاستعمارية . وبعد استقراره بأم العرائس في تونس , انخرط في العمل الثوري هناك, متوليا العديد من المسؤوليات, فكان مسؤول مدني يعمل على تأمين متطلبات المجاهدين, وجمع الاشتراكات والاحتفاظ بالوثائق الثورية, وجمع الأسلحة, و تجنيد الشباب للالتحاق بصفوف المجاهدين . وبعد الاستقلال مباشرة عاد إلى أرض الوطن و قد اكتسب خبرة أهلته لأن يتقلد العديد من المناصب, حيث كان من المعلمين الأوائل في منطقة حاسي خليفة, ليصبح بعد ذلك مديرا كما لم يتوقف عمله في قطاع التعليم فقط, بل كان له دور في المجال السياسي وذلك بانخراطه في المجلس البلدي و الولائي, حيث ساهم بشكل كبير في النهوض بمنطقته، وذلك من خلال تكوين جيل مثقف, بالإضافة إلى توليه رئاسة هيئة أولياء التلاميذ لمتوسطة شراحي مصباح, و ثانوية هواري بومدين, ثم اماما و خطيبا بإحدى مساجد المنطقة ومدرّسا للقرآن الكريم, كما كان له فضل في جلب العديد من المشاريع التربوية لهذه المنطقة إذ توفي رحمه الله يوم 28 اكتوبر 2006م عن عمر ناهز 76 سنة بعد صراع طويل مع المرض . "Mujahid lAzhari Awinat was born in 1930 in the village of Hassi Khalifa. He was keen to memorize the Holy Quran from an early age. As a young man, he immigrated to Tunisia in search of a livelihood and to escape colonial policy. After settling in Umm al-Ara'is in Tunisia، he became involved in revolutionary work there، assuming numerous responsibilities. He was a civilian official, working to secure the needs of the mujahideen, collect subscriptions، preserve revolutionary documents، collect weapons، and recruit young men to join the ranks of the mujahideen. Immediately after independence، he returned to his homeland, having gained experience that qualified him to hold many positions، as he was one of the first teachers in the Hassi Khalifa region, and then became a director. His work in the education sector did not stop only، but he also played a role in the political field by joining the municipal and state council، where he contributed greatly to the advancement of his region، through the formation of an educated generation, in addition to assuming the presidency of the Parents Association of the Sharahi Misbah Intermediate School، and Houari Boumediene High School، then an imam and preacher in one of the mosques in the region and a teacher of the Holy Quran. He also had the merit of bringing many educational projects to this region، as he died، may God have mercy on him, on October 28، 2006 AD، at the age of 76 years، after a long struggle with illness. "
مذكرة ماستر قسم علوم انسانية تخصص تاريخ المغرب العربي المعاصر
Keywords: أم العرائس; العمل الثوري; الهجرة إلى تونس; الأزهاري عوينات; Al-Azhari Awinat; Migration to Tunisia; Revolutionary Action; Mother of Brides